Empowered Women & Social Media: Analyzing #YourBeautyRules in Cyberfeminism Perspective - Nicky Lestari; Andi Nur Fadilah; Eka Wenats Wuryanta (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
This research aims to explain about cyberfeminism. It is a part of the new media discourse, discussing mainly the context of the development and empowerment of women. The main approach of this research was a qualitative approach, which included research methods of literature and documentative studies. This method mostly analyzed content through the perspective of cyberfeminism and how the Female Daily Network built campaigns through #YourBeautyRules content. This research showed that the campaign was built with narratives based on the experiences of FDN employees and some vloggers in Indonesia. This campaign has the potential to educate, motivate, and develop women so that they can prioritize character and self-development.